Parenting scale self-test: study of psychometric properties - Matos, Ana (2018)
Introduction: The Parenting Scale Self-Test (Gottman & Declaire, 1997) evaluates what parents think about emotions and the way they react to them. It also tries to determine the ways by which the parents teach their children to recognize, express and deal with emotions. Objective: The aim of this study is to evaluate some psychometric properties of PSST, namely its factorial structure and internal consistency. Methods: The sample consisted of 335 parents (65.07% female and 34.93% male) whose children are between 14 and 20 years of age. An exploratory factorial analysis was conducted using the principal components method with direct oblimin rotation. Results: The structure of the scale changed from the original, presenting in the Portuguese sample three parenting styles towards emotions: disapproving, explorer and accepting styles. The internal consistency of the scale showed alpha values of .87, .85 and .70, respectively. Conclusions: This research constitutes an initial step in the study and adaptation of the psychometric properties of the PSST in a sample of the Portuguese population, and is an important contribution for future research and clinical practice.